Relasi Gap Optis dengan Struktur Ikatan Lapisan Tipis Amorf Silikon Karbon (a-SiC:H) Hasil Deposisi Metode DC Sputtering - Rosari Saleh; Lusitra Munisa (Indonesian Journal of Physics, 2003)
The influence of hydrogen and carbon incorporation on the optical gap of amorphous silicon carbon (a-SiC:H) films deposited by dc sputtering methods were observed and analysed using ultra violet-visible (UV-VIS) and infrared spectroscopy. Hydrogen content NH and carbon concentration NC in the films increases considerably with increasing methane flow rate. Both hydrogen and carbon content induces the widening of the optical gap through its linear relation with Si-H, C-H and Si-C vibration absorption. For low methane flow rate, the widening of optical gap is mainly due to an increase of hydrogen content. The incorporation of carbon led to increase the optical gap for higher methane flow rate.